Notes on the preliminary ruling on the responsibility to examine a claim for asylum (Academic Journal of Internal Affairs, 2016)
The author provides and overview of the background and context of the request for preliminary ruling before the Court of Justice of the European Union on the issue of the general relation between the so called “Dublin regime” and the safe third country notion and specifically the meaning of the Article 3 para (3) of the Dublin III regulation.
Keywords: migration; preliminary ruling; Dublin III regulation